Modulation of muscle fuel metabolism in human volunteers by increasing the availability of muscle acetyl-CoA and carnitine moieties - Ghasemi, Reza (2016)
This thesis investigated the impact of sodium acetate infusion on muscle fuel metabolism during low and high intensity exercise and demonstrated a decrease in fat oxidation during the former and a decrease in muscle lactate production during the latter. We propose that the rate of fat oxidation decreased during low intensity exercise due to acetate being preferentially metabolised over fat and possibly reduced muscle free carnitine availability. During high intensity exercise, muscle lactate accumulation decreased due to higher acetyl-CoA supply to the TCA cycle.